Green Six sigma : a lean approach to sustainable climate change initiatives - Basu, Ron (Wiley, 2021)
Apply the tried-and-tested principles of Six Sigma to the fight against climate change In this much needed book, Dr Ron Basu delivers an insightful exploration as well as sage advice on how to apply the principles of Lean Six Sigma to today's climate crisis. Green Six Sigma: A Lean Approach to Sustainable Climate Change Initiatives is an adaption of Lean Six Sigma for climate change initiatives. How can we use Green Six Sigma urgently and effectively to reduce greenhouse gas emissions and adapt to the harmful effects of global warming? This practical and workable book covers topics that are highly relevant to the times we live in: Climate change challenges and initiatives to mitigate them Examination of the Green Six Sigma approach, its tools and techniques as well as modifications to incorporate both the digital revolution and sustainability Applications of the Green Six Sigma approach to a variety of areas relevant to climate change and in all economic sectors including energy, transport, manufacturing, services and agriculture Green Six Sigma in retrofitting houses and climate adaptation Guides to the implementation of sustainable climate change initiatives This book is an eye-opening resource, perfect for anyone responsible for sustainability or climate change initiatives at their organisations, NGOs or regulatory agencies. It is also a must-read for academics, managers, participants and practitioners of Six Sigma and Operational Excellence.